Pregunta
upstudy study bank question image url

Evaluate the integral. (Remember to use absolute values where appropriate. Use \( C \) for the constant of integration. \[ \int \frac{8}{(x-1)(x+7)} d x \]

Ask by Cummings Warner. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The integral evaluates to \( \ln \left| \frac{x - 1}{x + 7} \right| + C \).

Solución

To evaluate   ∫ [8/((x - 1)(x + 7))] dx, we begin by expressing the integrand as partial fractions. Write   8/[(x - 1)(x + 7)] = A/(x - 1) + B/(x + 7). Multiply both sides by (x - 1)(x + 7) to get   8 = A(x + 7) + B(x - 1). To find A and B, choose convenient values for x: 1. Let x = 1:   8 = A(1 + 7) + B(1 - 1) = 8A + 0  ⟹ A = 1. 2. Let x = -7:   8 = A(-7 + 7) + B(-7 - 1) = 0 + (-8B)  ⟹ -8B = 8  ⟹ B = -1. Thus, the decomposition is   8/[(x - 1)(x + 7)] = 1/(x - 1) - 1/(x + 7). Now, the integral becomes   ∫ [1/(x - 1) - 1/(x + 7)] dx. Integrate term by term:   ∫1/(x - 1) dx = ln|x - 1| + C₁,   ∫1/(x + 7) dx = ln|x + 7| + C₂. So the entire integral is   ln|x - 1| - ln|x + 7| + C, which can also be combined into a single logarithm:   ln |(x - 1)/(x + 7)| + C. Thus, the evaluated integral is   ln |(x - 1)/(x + 7)| + C.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To evaluate the integral \[ \int \frac{8}{(x-1)(x+7)} \, dx, \] we can use partial fraction decomposition. We first express the integrand as: \[ \frac{8}{(x-1)(x+7)} = \frac{A}{x-1} + \frac{B}{x+7}, \] where \( A \) and \( B \) are constants we need to solve for. Multiplying through by the denominator \( (x-1)(x+7) \) gives: \[ 8 = A(x+7) + B(x-1). \] Expanding the right-hand side, we have: \[ 8 = Ax + 7A + Bx - B = (A + B)x + (7A - B). \] To satisfy this equation for all \( x \), the coefficients of \( x \) must match and the constant terms must match: 1. \( A + B = 0 \) 2. \( 7A - B = 8 \) From the first equation, we can express \( B \) in terms of \( A \): \[ B = -A. \] Substituting \( B = -A \) into the second equation gives: \[ 7A - (-A) = 8 \implies 7A + A = 8 \implies 8A = 8 \implies A = 1. \] Now substituting \( A = 1 \) back to find \( B \): \[ B = -1. \] Thus, we have: \[ \frac{8}{(x-1)(x+7)} = \frac{1}{x-1} - \frac{1}{x+7}. \] Now we can integrate each term separately: \[ \int \frac{8}{(x-1)(x+7)} \, dx = \int \left( \frac{1}{x-1} - \frac{1}{x+7} \right) \, dx. \] This gives: \[ = \int \frac{1}{x-1} \, dx - \int \frac{1}{x+7} \, dx = \ln |x-1| - \ln |x+7| + C. \] Using the properties of logarithms, we can combine these terms: \[ = \ln \left| \frac{x-1}{x+7} \right| + C. \] Finally, the evaluated integral is: \[ \int \frac{8}{(x-1)(x+7)} \, dx = \ln \left| \frac{x-1}{x+7} \right| + C. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad